Antibacterial potential of silver nanoparticles (SP-AgNPs) synthesized from Syzygium polyanthum (wight) Walp. against selected foodborne pathogens - Khan, Sadeeya; Rukayadi, Yaya; Jaafar, Anmad Haniff; Ahmad, Nurul Hawa (Elsevier BV, 2023)
Foodborne diseases continue to pose a significant global health concern, causing a considerable number of deaths worldwide. In response to concerns surrounding bacterial resistance and the limitations of traditional antibiotics, there is a growing interest in exploring natural antibacterial agents as potential alternatives for addressing foodborne pathogens. Nowadays efforts are being made on exploring the potential of natural antibacterial agents against foodborne pathogens. In this study, the antibacterial efficacy of silver nanoparticles synthesized using S. polyanthum leaves extract (SP-AgNPs) against selected Gram-negative and Gram-positive foodborne pathogens was investigated by using multiple assays, including the well diffusion assay (WDA), minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-kill assay. The well diffusion assay demonstrated the inhibitory potential of SP-AgNPs against all tested foodborne pathogens, with inhibition zones ranging from 10.16 + 1.25 to 13.16 + 1.52 mm. Furthermore, the MIC values ranged from 0.008 to 0.125 mg/mL, indicating the potent antibacterial activity of SP-AgNPs across a broad spectrum of foodborne pathogens. The MBC values, ranging from 0.008 to 0.250 mg/mL, further confirming the bactericidal ability of SP-AgNPs against these pathogens. In the time-kill experiment, most foodborne pathogens were entirely killed after 4 h of incubation at 4 — MIC concentration. However, only E. coli, K. pneumoniae, and S. Typhimurium showed a reduction in population to 3 Log10¯CFU/mL, indicating a strong bactericidal effect of SP-AgNPs on most tested pathogens. In conclusion, this study provides compelling evidence that SP-AgNPs exhibit potent antibacterial activity against selected foodborne pathogens. The findings suggest that SP-AgNPs synthesized using S. polyanthum leaves extract hold great promise as a novel antibacterial agent for effectively controlling foodborne pathogens. These findings contribute to continuing efforts in developing alternative strategies to prevent foodborne diseases and enhance food safety.